THE EFFECT OF OUTDOOR LEARNING-BASED PROBLEM-BASED LEARNING MODEL ON LEARNING OUTCOMES IN TERMS OF STUDENT ACTIVITY IN ECOSYSTEM MATERIAL CLASS VII MTS NEGERI 4 BOJONEGORO - Nikma, Julia Khoirun; Anfa, Qurrotul; Agnafia, Desi Nuzul (International Journal Multidisciplinary (IJMI), 2024)
This study aims to determine the effect of outdoor learning-based problem-based learning model on student learning outcomes in terms of student activity in class VII ecosystem material at MTs Negeri 4 Bojonegoro. The research design in this study used Pre-test Post-test Control Groub Design using two classes, namely the experimental class and the control class. The sampling technique used Simple Random Sampling. The samples used were class VII E as the experimental class and class VII F as the control class. The data collection technique used test questions consisting of 10 items in the form of descriptions to measure student learning outcomes and student activity observations consisting of 15 statements with yes and no answers. Data analysis techniques use pre-requisite tests in the form of validity, reliability, normality and homogeneity tests while hypothesis testing uses one way anava test. The results obtained from this study are the average post-test results of the experimental class of 80.29 and the control class of 77.10 which can be concluded that the increase in student learning outcomes using the Outdoor Learning-based Problem Based Learning model is better than the indoor Problem Based Learning model